Comics studies a guidebook - Beaty, Bart; Hatfield, Charles
Nominee for the 2021 Eisner Awards Best Academic/Scholarly Work In the twenty-first century, the field of comics studies has exploded. Scholarship on graphic novels, comic books, comic strips, webcomics, manga, and all forms of comic art has grown at a dizzying pace, with new publications, institutions, and courses springing up everywhere. The field crosses disciplinary and cultural borders and brings together myriad traditions. Comics Studies: A Guidebook offers a rich but concise introduction to this multifaceted field, authored by leading experts in multiple disciplines. It opens diverse entryways to comics studies, including history, form, audiences, genre, and cultural, industrial, and economic contexts. An invaluable one-stop resource for veteran and new comics scholars alike, this guidebook represents the state of the art in contemporary comics scholarship.